Factors Associated with Readmissions in Ischemic Stroke : A Literatur Review - Ni Made Ratih Comala Dewi; Ni Luh Putu Dina Susanti; I Kadek Nuryanto; Ni Kadek Sutini (Babali Nursing Research, 2025)
Background: Readmission cases among stroke patients are common, with only 15% of patients surviving and avoiding readmissions over a five-year period. Ischemic stroke patients who are readmitted face a higher risk of death and significantly increased healthcare costs. Therefore, identifying factors associated with the readmission of ischemic stroke patients is essential to prevent these occurrences. Methods: Articles were selected following PRISMA Guidelines. A literature review used three journal databases: ScienceDirect, PubMed, and Google Scholar. Keywords were aligned with the Medical Subject Heading (MeSH) terms, including "readmission," "ischemic stroke," and "risk factors." Several inclusion criteria were applied to identify eligible articles: publication between 2014 and 2023 and written in English or Bahasa. Sixteen eligible articles were ultimately included in the analysis. Results: A total of 16 articles were reviewed (n = 354,682). The causes of readmission in ischemic stroke patients were categorized into two groups: neurological and non-neurological disorders. Seven common comorbidities were identified as risk factors: hypertension, cardiovascular diseases, diabetes, dyslipidemia, obesity, previous stroke events, and stroke recurrence. Conclusion: The review revealed significant variation in readmission rates among ischemic stroke patients, ranging from 6.7% to 74% within 28 days to 10 years. This trend was particularly pronounced among adults and older women. These findings provide valuable insights for initiatives to prevent patient readmissions and highlight the importance of improving future care quality.